A Covalently Integrated Reduced Graphene Oxide–Ion‐Exchange Resin Electrode for Efficient Capacitive Deionization. Issue 5 (18th January 2021) - Islam, Md Rabiul; Gupta, Soujit Sen; Jana, Sourav Kanti; Srikrishnarka, Pillalamarri; Mondal, Biswajit; Chennu, Sudhakar; Ahuja, Tripti; Chakraborty, Amrita; Pradeep, Thalappil
Abstract: Capacitive deionization (CDI) is an emerging, cost‐effective alternative for energy‐efficient desalination technology. Efficient electrode materials based on individual reduced graphene oxide (rGO) nanosheets are produced by functionalizing them with polystyrene (rGO–PS) through an in situ polymerization process involving rGO, styrene monomer, and divinylbenzene. The rGO–PS‐integrated composite nanostructures are subsequently functionalized with sulfonate and quaternary amine functionalities to achieve positively and negatively charged electro‐adsorbent ion‐exchange resins (EAIERs), respectively. These EAIERs 'molecular constructs' are used to fabricate CDI electrodes, and deionization is performed to remove various ions. These molecular constructs promote faster charge transfer at the electrode–electrolyte interface and maintained the electrical conductivity of the active rGO. This leads to a high electroadsorption capacity of 15.93 mg g −1 of Cl − using NaCl solution with a conductivity of 802 µS in laboratory batch experiments, which is approximately five times higher than the adsorption capacity of rGO electrodes reported earlier (≈2–3 mg g −1 ) in comparable experimental conditions. No significant Faradaic redox reactions or chemical changes are observed on the electrode surface, which make these electrodes exhibit excellent electrochemical stability even after multiple adsorption/desorption cycles. Abstract : Electro‐adsorbent ion‐exchange resin molecular constructs are synthesized through covalent functionalization of positive and negative ion‐exchange resins with reduced graphene oxide. These molecular functionalized electrodes show a high salt uptake capacity of 15.93 mg g −1 due to the large electrochemical surface area and hierarchically porous structure.